Respon Pertumbuhan Bibit Kopi Arabika (Coffea arabica) Varietas Catuwai Terhadap Pemberian Zat Pengatur Tumbuh Ekstrak Tauge - Berlian Zetikarya Haryati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2020)
Research on the Growth Response of Arabica Coffee Seeds (Coffea arabica) of the Catuwai Variety to the Giving of ZPT Bean Sprouts Extract, was carried out in February - June 2020 at the Arabica coffee plantation of PT. Sulotco Jaya Abadi, Lembang Tiroan, Bittuang District, Tana Toraja Regency at an altitude of 1400 m asl with climate type A (Scmidt and Ferguson), the study aims to determine the appropriate concentration for the growth of Arabica coffee seedlings of the Catuwai Variety. The study was arranged using a Completely Randomized Design ( RAL) with a single factor treatment consisting of 5 treatment levels in the form of concentrations E¬0: no treatment, E1: 10 ml/l water, E2:20 ml/l water, E3: 30 ml/l water and E4: 40 ml/ l water. Each treatment was repeated 3 times, and in each treatment plot there were 8 plant seeds (6 sample plants and 2 destructive plants) so that there were 120 plants. The results showed that the best treatment was at a concentration of 30 ml/l water, especially for the components of plant height, number of leaves, and stem diameter and concentration of 20 ml/l water for root volume.